2010
DOI: 10.1128/aac.01409-09
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cotrimoxazole on Carriage and Antibiotic Resistance of Streptococcus pneumoniae and Haemophilus influenzae in HIV-Infected Children in Zambia

Abstract: This is a substudy of a larger randomized controlled trial on HIV-infected Zambian children, which revealed that cotrimoxazole prophylaxis reduced morbidity and mortality despite a background of high cotrimoxazole resistance. The impact of cotrimoxazole on the carriage and antibiotic resistance of Streptococcus pneumoniae and Haemophilus influenzae as major causes of childhood mortality in HIV-infected children was investigated since these are unclear. Representative nasopharyngeal swabs were taken prior to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
29
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 52 publications
9
29
4
Order By: Relevance
“…aureus (60.4% in children between 10 and 15 years) was similar to those reported from industrialized countries [18]. Colonization with H. influenzae was lower compared with reports from Kenya and South Africa (12% versus 20-30%) [19,20]. Recently, a sequence-based study revealed that 27.3% of nasopharyngeal H. influenzae isolates, identified by biochemical standard methods, were in fact H. haemolyticus [13].…”
Section: Discussionsupporting
confidence: 69%
“…aureus (60.4% in children between 10 and 15 years) was similar to those reported from industrialized countries [18]. Colonization with H. influenzae was lower compared with reports from Kenya and South Africa (12% versus 20-30%) [19,20]. Recently, a sequence-based study revealed that 27.3% of nasopharyngeal H. influenzae isolates, identified by biochemical standard methods, were in fact H. haemolyticus [13].…”
Section: Discussionsupporting
confidence: 69%
“…Another study in a post-Hib vaccination setting reported that H. influenzae carriage rates were lower in children aged ≥10 years and adults (1.1%–3.9%) than in children <10 years (21.0%–29.0%) [55]. The prevalence of H. influenzae carriage in HIV-infected children was reported for India (24%) [70] and Zambia (29%) [71], two lower-middle income countries. The prevalence of H. influenzae carriage in ill children from three lower-middle income countries ranged between 15.2% and 53.5% [36], [61], [62].…”
Section: Resultsmentioning
confidence: 99%
“…Given that the supply of these drugs is known to be erratic, this raises the possibility of increased background rates of resistance in M. tuberculosis (6,9,13). This should be considered carefully when evaluating the prospect of TMP-SMX for treatment of tuberculosis (8,14,17).…”
mentioning
confidence: 99%